2009
DOI: 10.1590/s1020-49892009001100004
|View full text |Cite
|
Sign up to set email alerts
|

Alimentação complementar de lactentes em uma cidade desenvolvida no contexto de um país em desenvolvimento

Abstract: The median duration of exclusive breastfeeding was far from that recommended due to the offer of supplementary fluids. Supplementary foods were introduced precociously, especially sweets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
14

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 16 publications
1
17
0
14
Order By: Relevance
“…Among Brazilian state capitals and the Federal District the median value is of 54.1 days 14 , another study found a median value of 90 days 17 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Among Brazilian state capitals and the Federal District the median value is of 54.1 days 14 , another study found a median value of 90 days 17 .…”
Section: Discussionmentioning
confidence: 94%
“…This fact was also found in the study of Garcia et al,¹ in which 29.6% of the children of from 6 to 8 months had still not received a salt meal and 20% of these children received only liquids. In the study of Brunken et al, 28 one part of the children investigated also did not take fruit at 12 months of age and there were still children who, at 8 months of age, did not eat meat, beans or soup, in another research project 17 there was also some delay in the offer of fruit, vegetables and eggs to some children.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although few studies have described time trends in indicators of early complementary 10 . Nonetheless early complementary feeding it is still common in Brazil 19,20 . Meanwhile, it is not easy to compare our findings with those from the literature on indicators of complementary feeding patterns among children from 6 to 11.9 months of age, given that the few studies providing information on complementary feeding patterns use different indicators from ours, and do not present time trends for complementary feeding patterns in the second semester of life 10,13,21 .…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of foods can interfere with the absorption of the iron present in breast milk, so it is very important that complementary foods are iron-rich, such as meat or offal, and are sources of vitamin C, which contributes to the absorption of non-heme iron present in foods such as dark green vegetables 17 , 13 …”
Section: Discussionmentioning
confidence: 99%